Improving Students’ Mathematical Creative Thinking Ability and Motivation through Problem-Based Learning Model - Marbun, Yanty Maria Rosmauli (Indonesian Journal of Multidisciplinary Science, 2023)
This study aims to determine the mathematical creative thinking ability of students after being taught with the Problem Based Learning (PBL) learning model. This research is a quasi-experimental research that compares two learning models, namely, the problem-based learning model and the conventional learning model, and is designed as follows: (i) a research sample of 60 students was selected as the research sample, and (ii) the data from the research test of students' mathematical creativity ability was carried out 2 (two), namely pretests (before learning) and postes (after learning). From the results of the research, it can be concluded that the average pretest score of mathematical problem solving ability also increased in the control class, especially for fluency indicators, but from the average of the two classes, the average in the experimental class was higher than the control, which was 53.33%. The average N-gain of creative thinking abilities of students taught with PBM was 0.48 and in students teaching with conventional learning. It was known that the increase in student motivation that obtains a PBM is higher than those whose learning uses ordinary learning. Therefore, it is important for schools to socialize PBM to be applied in the learning process so that it can improve students' mathematics skills, especially the ability to think creatively mathematically and student learning motivation.